Evaluasi Kesesuaian Lahan Tanaman Padi Sawah, Padi Gogo (Oryza sativa L.), Dan Sorgum (Shorgum bicolor) Di Kecamatan Sei Bamban Kabupaten Serdang Bedagai - waskito waskito; Purba Marpaung; Alida Lubis (Universitas Sumatera Utara, 2017)
This study aimed to evaluate the suitability of land on rice, upland rice and sorghum crops in Sei Bamban SubDistric of Serdang Bedagai District. It can be obtained 3 Land Mapping Units (SPL) which is determined based on the overlay result from the soil type map, slope maps and altitude map that is Inceptisol SPL 1, Ultisol SPL 2, and Ultisol SPL 3. This study used survey method. The results showed that the land suitability classes of actual rice and upland rice crops in the SPL 1 and SPL 3 is Marginally Suitable/S3nr by a nutrient retention barrier factor, for rice crops in the SPL 2 is Suitable/S2nr, and Suitable/S2wanr for upland rice crops with the barrier factor of excessive water availability (wa). While the potential classes of land suitability for rice and upland rice crops is Very Suitable/S1 for SPL 1, 2 and 3. The suitability class for actual sorghum crops on SPL 1, 2, and 3 is Not Suitable/Nwa with the barrier factor of excessive water availability (wa). While the potential land suitability classes is Suitable/S2tcwa by the barrier factor of temperature (tc) and the excessive water availability (wa) for SPL 1, 2, and 3. The conclusion is the low production of rice crops (55,96 qw/ha) on Inceptisol SPL 1 due to low C-organic content. On Ultisol SPL 2 due to low C-organic content and clay CEC. On Ultisol SPL 3 due to low C-organic content, clay CEC, and the slope is a little bit ramped.